PENGARUH CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE TERHADAP RETURN SAHAM PADA PERUSAHAAN INDEKS LQ-45 YANG LISTED DI BURSA EFEK INDONESIA (BEI) - Astrid Maharani (Universitas Muhammadiyah Jember, 2017)
Abstract: The aim of this study was examine the effect of stock return practice amonglisted high profile companies at Indonesia Stock Exchange. The factors being examined was Corporate Social Responsibility disclosure. CAR is used todetermine stock return. The study using 56 firm-years of LQ-45 companies listed in Indonesia Stock Exchange, with period between 2013-2014. The hypothesis was tested using linier regression. Both F-test dan t-test have also been used to test the significance of the study hypothesis. Linier regression showed that both partially and simultaneosly, Corporate Social Responsibility disclosure didn’t prove to have a significant influence on stock return.Keywords: Corporate Social Responsibility, Disclosure, LQ-45, Stock return